2009
DOI: 10.1007/s00330-008-1288-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumour enhancing fraction (EnF) in glioma: relationship to tumour grade

Abstract: The aim of this research was to determine whether the proportion of a tumour that enhances (enhancing fraction, EnF) and changes in EnF with enhancement threshold differ between low and high grade glioma. Forty-four patients (45 gliomas comprising 16 grade II, 5 grade III and 24 grade IV) were studied. Imaging included pre-and post-contrast-enhanced T 1 -weighted sequences and T 1 -weighted DCE-MRI. Thresholded enhancement maps were generated for each tumour by using a range of values of the initial area under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In a previous study, we have demonstrated that EnF defined at a threshold of IAUC 60 Ͼ 2.5 mmol.s pro-vides optimal discrimination between low-and high-grade gliomas. 29 The value of EnF in an individual tumor will be affected by a number of variations in the tumor vascular microenvironment. Areas of necrosis or nonperfusion will clearly fail to enhance, but enhancement may also not occur in viable tumor if perfusion pressure and perfusion rates are low relative to the vascular half-life of the contrast media.…”
mentioning
confidence: 99%
“…In a previous study, we have demonstrated that EnF defined at a threshold of IAUC 60 Ͼ 2.5 mmol.s pro-vides optimal discrimination between low-and high-grade gliomas. 29 The value of EnF in an individual tumor will be affected by a number of variations in the tumor vascular microenvironment. Areas of necrosis or nonperfusion will clearly fail to enhance, but enhancement may also not occur in viable tumor if perfusion pressure and perfusion rates are low relative to the vascular half-life of the contrast media.…”
mentioning
confidence: 99%
“…A number of patients with cerebral tumours will have a CT scan as their initial investigation, but the imaging modality of choice for brain tumour characterisation is an MRI scan and therefore the ability to derive a signal intensity based MRI measure of EnF was assessed in the current study as opposed to a CT based measure. A study of DCE-MRI derived EnF in glioma has shown the use of thresholding allows the distinction between histological grade of tumour [3]. In the unthresholded form, EnF IAUC60>0 correlated with v p in low grade tumours and K trans in GBM [2].…”
Section: Discussionmentioning
confidence: 99%
“…EnF is a relatively recently described parameter [2,3,20,21]. A CT variant of this measure has shown potential in predicting disease free survival and time to progression in patients with ovarian carcinoma [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations